SERIBU (Cerita Seru Bersama Ibu) untuk Mengembangkan Kemandirian Anak Usia 4-5 Tahun di Kp Bangbayang Selatan Kota Bandung - Indriani Susan; Aep Saepudin; Dewi Mulyani (UNISBA Press, 2022)
Abstract. The background of this skripsi takes place in the village of South Bangbayang, Bandung City. Because parents are busy working and there are some parents who just have one child, so the needs of children are always catered for. The purpose of this study was to see the development of the independence of children aged 4-5 years in South KP Bangbayang, Bandung City through SERIBU activities (exciting stories with mothers). The specific purpose is to describe and find out the SERIBU program at home, the implementation of the SERIBU program and the assessment of the independence of children 4-5 years old through the SERIBU program in South Bangshadow Village, Bandung City. The method used in this study uses a qualitative descriptive approach, namely to obtain the development of independence of children aged 4-5 years in South Bangshadow Village through the SERIBU program so that researchers will describe the results of observations and interviews. The subjects in this study were 4-5 years old at Rt 01 Rw 09 Kp Bangshadow Selatan Bandung City and data collection techniques were interviewed to parents. The results obtained from the SERIBU program regarding the independent development of children aged 4-5 years in South Bangshadow Village, Bandung City include: 1) Children are able to wear and undress themselves; 2) Children are able to put on and take off their own shoes; 3) Children are able to feed themselves; 4) Children are able to choose and find toys after using them; 5) Children are able to learn to bathe, urinate and defecate on their own; 6) Children are able to do the tasks given by their parents at home. Abstrak. Latar belakang skipsi ini terjadi di kampung Bangbayang Selatan Kota Bandung. Karena kesibukan orang tua bekerja dan ada beberapa orang tua yang baru memiliki anak satu sehingga kebutuhan anak selalu dilayani. Tujuan dalam penelitian ini untuk melihat perkembangan kemandirian anak usia 4-5 tahun di Kp Bangbayang Selatan Kota Bandung melalui kegiatan SERIBU (cerita seru bersama ibu). Adapun tujuan khusus untuk mendiskripsikan dan mengetahui perencanaan program SERIBU dirumah, pelaksanaan program SERIBU dan penilaian perkembangan kemandirian anak 4-5 tahun melalui program SERIBU di Kp Bangbayang Selatan Kota Bandung. Metode yang digunakan dalam penelitian ini menggunakan pendekatan Deskritif Kualitatif yaitu untuk memperoleh perkembangan kemandirian anak usia 4-5 tahun di Kp Bangbayang Selatan melalui program SERIBU sehingga peneliti dan yang diteliti akan di deskripsikan sebagai hasil observasi dan wawancara. Subjek dalam penelitian ini yaitu anak usia 4-5 tahu di Rt 01 Rw 09 Kp Bangbayang Selatan Kota Bandung dan pengumpulan teknik data mengunakan wawancara kepada orang tua. Adapun hasil yang diperoleh dari program SERIBU mengenai perkembangan kemandirian anak usia 4-5 tahun di Kp. Bangbayang Selatan Kota Bandung diantaranya: 1) Anak mampu memakai dan membuka baju sendiri; 2) Anak mampu memakai dan membuka sepatu sendiri; 3) Anak mampu makan sendiri; 4) Anak mampu memilih dan membereskan mainan setelah menggunakannya; 5) Anak mampu belajar mandi, BAK dan BAB sendiri; 6) Anak mampu mengerjakan sendiri tugas yang diberikan orangtua dirumah.